ZnO/fly ash catalyst for producing biodiesel from kapok seed (Ceiba pentranda) oil - Novantri, Decky Achmad; Innarta, Yahya Dwi Adhitya; Somawiharja, Yohaness; Chern, Jiang-Min; Asri, Nyoman Puspa (Universitas Lambung Mangkurat, 2024)
The quantity of fossil fuels has decreased every year due to increasing energy consumption, thereby requiring alternative renewable energy sources such as biodiesel from kapok seeds. Basically, making biodiesel needs a catalyst. Catalysts are classified into two types based on their phase: homogeneous and heterogeneous. This research employed a ZnO heterogeneous catalyst with fly ash support. It investigated the optimal mole ratio of catalyst and kapok seed oil as well as the optimal catalyst dose to produce the best biodiesel yield. The methodology in this study consisted of ZnO preparation, fly ash preparation, ZnO/fly ash catalyst synthesis, and biodiesel production by the transesterification reaction process. The research variables included the dose of catalyst (wt% oil) of 3, 4, 5, 6, and 7 and the mole ratios of oil to methanol of 1:9, 1:12, 1:15, 1:18, and 1:21. The results of this study indicated that the best catalyst dose was 5% with a biodiesel yield of 58%. Meanwhile, the variable molar ratio of oil to methanol got the highest yield of 65% at 1:8. Therefore, a zinc oxide catalyst with fly ash as support had great potential to produce biodiesel from kapok seed oil.Keywords: Biodiesel; Kapok Seed Oil; ZnO; Fly ash; Yield